Hubungan Riwayat Imunisasi dengan Status Gizi Balita: The Relationship between Immunization History with Nutrition Status among Under-five Children - Siti Nurhasiyah Jamil; Aning Subiyatin (Jurnal Bidan Cerdas, 2020)
The toddler period is a period that must be observed property, at this time the direction of child development will be determined for the next period. The purpose of this study was to study the immunization status of nutritional status in infants. The research design used was cross-sectional in the work area of Johar Baru Health Center, Jakarta Pusat, which was conducted from April–June 2019. The population of all children aged 6-59 months, while the study sample was infants with stunting of 105 respondents, which is data child nutrition in Health Center. Data processing and analysis using SPSS with Chi-Square statistical test, the confidence level of 95%. The results of variables related to the nutritional status of children under five are the relationship of immunization P value (0.004 OR and CI (0.173 (0.051-0.59). The conclusion of the variable related to the nutritional status of under-five children is immunization.